Decline in prevalence of human papillomavirus infection following vaccination among Australian Indigenous women, a population at higher risk of cervical cancer: The VIP-I study. Issue 29 (5th July 2018) - McGregor, Skye; Saulo, Dina; Brotherton, Julia M.L.; Liu, Bette; Phillips, Samuel; Skinner, S. Rachel; Luey, Michele; Oliver, Lisa; Stewart, Mary; Tabrizi, Sepehr N.; Garland, Suzanne; Kaldor, John M.
Highlights: Higher rates of cervical cancer in Australian Indigenous women vs. non-Indigenous women. Repeat cross-sectional study investigating HPV infection rates in Indigenous women. The proportion found to have HPV vaccine types declined by 94%, from 24 to 1.4%. Evidence of the success of Australia's HPV vaccination program. Abstract: Background: Cervical cancer occurrence and mortality are strongly correlated with socioeconomic disadvantage, largely due to unequal access to screening and treatment. Universal human papillomavirus (HPV) vaccination provides the opportunity to greatly reduce this global health disparity. Australian Indigenous women have substantially higher rates of cervical cancer than non-Indigenous women, primarily due to under-screening. We investigated HPV infection rates in Indigenous women 7 years after implementation of the national HPV vaccination program. Methods: We used a repeat cross-sectional design, with the baseline being provided by an HPV prevalence survey among Indigenous women attending clinics for cervical cytology screening, prior to the start of the vaccination program in 2007. We returned to clinics in four locations during 2014–15, and invited women aged 18–26 years attending for screening to provide a cervical specimen for HPV testing, as well as to complete a short questionnaire and consent to allow access of their records in the National HPV Vaccination Program Register. We used well-established laboratory methods to test specimens for specific HPV genotypes. Results: A total of 142 women were recruited at participating sites and compared to 155 who had been recruited at the same locations in the 2007 pre-vaccine survey. The two groups were identical in regard to age, with the more recent group having a higher proportion of hormonal contraception users, and a lower proportion of smokers. The proportion found to have any HPV type fell from 58 to 36% with the decline being entirely due to reductions in vaccine types, which fell by 94% from 24 to 1.4%. Conclusion: Australia's national HPV vaccination program appears to be successfully protecting a very high proportion of Indigenous women against vaccine targeted HPV types, who have in the past been at elevated risk of cervical cancer.